The Effect of Competence, Experience, and Placement on Employee Performance Bppsdm Ministry of Agriculture Jakarta with Motivation as Mediation Variable - Reza Apriansyah; Aslam Mei Nur Widigdo (Budapest International Research and Critics University, 2022)
This study aims to analyze how much influence competence, experience, and placement have on employee performance with motivation as a partially mediating variable in implementing this research using primary data obtained from the distribution of questionnaires. This research was conducted on employees of the agency of agricultural counseling and human resources development (BPPSDM) Ministry of Agriculture Jakarta, with a sample of 100 employees. The data analysis method used a structural equation model-partial least square (SEM-PLS). The study results show that the influence of competence, experience, and placement in the partial test has influenced employee motivation. The impact of competence, placement, and motivation can also encourage and affect employee performance. The results of this study indicate that experience has no significant effect on employee performance. This study shows that competence, experience, and placement affect employee performance mediated by motivation. The magnitude of this influence shows that competence, placement, and motivation are essential elements in improving employee performance BPPSDM Ministry of Agriculture Jakarta.